Valuation of the ecosystem services of recreation and tourism: a mechanism for the sustainable development of Forest Reserve Greece, Costa Rica - Hartley Ballestero, Marjorie (2021)
Study is addressed in the framework of the project “Ecosystem Services in the Hydrographic Basins of the Greater Metropolitan Area of Costa Rica”, that search, among other things, to contribute with conservation and preservation of the Bosque del Niño. This region is a remnant of the natural areas of the Greater Metropolitan Area; it also has high potential for the development of tourism activity, strongly linked to the natural characteristics of the region. For the estimation, the Referendum Type Contingent Valuation Method is used, where the individual must issue a binary answer (Yes or No). Since in the referendum model the dependent variable is discrete, the regression analysis is done using a logit model. The consulted people declare to give value of present and future existence to aspects such as biodiversity, pure air, and scenic beauty. At the same time, they express the value for the walks, the observation of animals. Knowing that these ecosystem services generate well-being, individuals are willing to pay for the conservation and preservation of the recreation site. In this sense, local and regional authorities must incorporate in their development plans the interest of communities to preserve these types of places for their current and future enjoyment. It also matters to improve the quality of these services, strongly linked to one of the most important economic activities in the region, such as tourism.